2016
DOI: 10.1111/bjdp.12161
|View full text |Cite|
|
Sign up to set email alerts
|

The space‐math link in preschool boys and girls: Importance of mental transformation, targeting accuracy, and spatial anxiety

Abstract: Spatial abilities are pertinent to mathematical competence, but evidence of the space-math link has largely been confined to older samples and intrinsic spatial abilities (e.g., mental transformation). The roles of gender and affective factors are also unclear. This study examined the correlations between counting ability, mental transformation, and targeting accuracy in 182 Hong Kong preschoolers, and whether these relationships were weaker at higher spatial anxiety levels. Both spatial abilities related with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 115 publications
3
23
0
Order By: Relevance
“…As male students are faced with the challenges of their first university-level physics course, the brain may accommodate the increases in science anxiety and balance the response to such challenges. In contrast, female students experience greater obstacles in STEM education 5,6,52 that can trigger anxiety as early as the preschool and elementary years [53][54][55] . The null female results may point to a lack of vulnerability, suggesting that their relatively higher STEM anxiety does not hinder salience-related central executive and self-referential processes.…”
Section: Discussionmentioning
confidence: 99%
“…As male students are faced with the challenges of their first university-level physics course, the brain may accommodate the increases in science anxiety and balance the response to such challenges. In contrast, female students experience greater obstacles in STEM education 5,6,52 that can trigger anxiety as early as the preschool and elementary years [53][54][55] . The null female results may point to a lack of vulnerability, suggesting that their relatively higher STEM anxiety does not hinder salience-related central executive and self-referential processes.…”
Section: Discussionmentioning
confidence: 99%
“…The article ‘The space‐math link in preschool boys and girls: Importance of mental transformation, targeting accuracy, and spatial anxiety’ by Wong was published in issue 35:2 of British Journal of Developmental Psychology ().…”
Section: Introductionmentioning
confidence: 99%
“…A more recent review of cognitive abilities also suggested a male advantages in some cognitive task from early childhood onwards (Miller & Halpern, 2014). Judging distances in space and projecting a trajectory with respect to a target require cognitive processes where males have shown an advantage (Uttal et al, 2013;Wong, 2017). Based on these results, we hypothesize that male participants will retain their upper hand in the virtual throwing task (alternative Hypothesis).…”
Section: Introductionmentioning
confidence: 85%
“…This visuomotor processing may require cognitive abilities where adult males have tended to show an advantage (Miller & Halpern, 2014;Wong, 2017). For example, males have performed better in tasks involving spatial perception and mental rotation, although not in spatial visualization (Voyer et al, 1995).…”
Section: Performance Errormentioning
confidence: 99%
See 1 more Smart Citation